Heat-shock protein 90 associates with N-terminal extended peptides and is required for direct and indirect antigen presentation - Callahan, Margaret K. (National Academy of Sciences, 2008)
CD8(+) T cells recognize peptide fragments of endogenously synthesized antigens of cancers or viruses, presented by MHC I molecules. Such antigen presentation requires the generation of peptides in the cytosol, their passage to the endoplasmic reticulum, loading of MHC I with peptides, and transport of MHC I–peptide complexes to the cell surface. Heat-shock protein (hsp) 90 is a cytosolic chaperone known to associate with peptide and peptide precursors of MHC I epitopes. We report here that treatment of cells with hsp90 inhibitors leads to generation of “empty” MHC I caused by inhibited loading of MHC I with peptides. Inhibition of hsp90 does not inhibit synthesis of MHC I, nor does it affect the activity of proteasomes. Hsp90-inhibited cells, such as proteasome-inhibited cells, are poor stimulators of T lymphocytes. The role of hsp90 in presentation of an ovalbumin epitope is shown to be at a postproteasomal step: hsp90 associates with N-terminally extended precursors of the SIINFEHL epitope, and such peptides are depleted from hsp90 preparations in hsp90-inhibited cells. Inhibition of hsp90 in the antigen donor cell compromises their ability to cross-prime. Conversely, stressed cells expressing elevated hsp90 levels show a heat-shock factor-dependent, enhanced ability to cross-prime. These results demonstrate a substantial role for hsp90 in chaperoning of antigenic peptides in direct and indirect presentation. The introduction of a stress-inducible component in these pathways has significant implications for their modulation during fever and infection.